Socioeconomic Impacts of COVID-19 in Kenya on Firms : Rapid Response Phone Survey, Round 1 - World Bank (World Bank, Washington, DC, 2021)
The COVID-19 pandemic has severe impacts on the Kenyan economy and society as a whole. This report analyzes the impact of COVID-19 on businesses in Kenya based on a nationally representative Business Pulse Survey implemented by the World Bank between June and August, 2020. The results indicate that about 93 percent of firms experienced a decline of sales compared to the same period of the previous year. Sales dropped by around 50 percent in the average and median Kenyan firms, and by more than 70 percent for one-quarter of firms. Close to 65 percent of firms are experiencing a decline in demand, cash flow, and available finance. Moreover, firms expect sales to continue declining in the coming months. The pandemic is disproportionally affecting small and female-owned businesses. Firms in Kenya are responding to the crisis through the adoption of digital technologies. About 20 percent of firms have received public support, but lack of awareness of public assistance options is still large among those that did not receive any support. Finally, the COVID-19 Business Pulse Survey (COV-BPS) suggests policy response options divided into four areas: access to finance, firm capabilities, access to new markets, and reducing uncertainty. Additional follow-up surveys are being conducted for monitoring the current circumstances and updating the policy recommendations.